2002
DOI: 10.1016/s0168-6496(02)00358-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response to temperature changes of the marine, sulfate-reducing bacterium Desulfobacterium autotrophicum

Abstract: The physiological response of bacteria to temperature is critical for the regulation of biogeochemical processes on daily, seasonal, and inter-annual time scales. We investigated the temperature response of the marine sulfate-reducing bacterium Desulfobacterium autotrophicum strain HRM2. Growth experiments in a temperature gradient block demonstrated that D. autotrophicum is psychrotolerant and grows between 0 and 31 ‡C. The normal range of temperature for growth is between 4 and 29 ‡C. The physiological respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The stress responses of H. uninervis and C. serrulata at 35°C were exacerbated by moderate and high p CO 2 , as it drove greater decline in net productivity, leaf extension, and shoot density. Temperature stress can be exacerbated by the addition of organic matter and the subsequent accumulation of sulphide in seagrass sediments (Koch et al ., ), which is a known phytotoxin, because the optimum temperature for microbial sulphide reduction is at 35–40°C (Wieland & Kühl, ; Rabus et al ., ), and increased p CO 2 may have also affected sediment condition. Z. muelleri is able to maintain an oxic microshield around its roots by pumping oxygen from its leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The stress responses of H. uninervis and C. serrulata at 35°C were exacerbated by moderate and high p CO 2 , as it drove greater decline in net productivity, leaf extension, and shoot density. Temperature stress can be exacerbated by the addition of organic matter and the subsequent accumulation of sulphide in seagrass sediments (Koch et al ., ), which is a known phytotoxin, because the optimum temperature for microbial sulphide reduction is at 35–40°C (Wieland & Kühl, ; Rabus et al ., ), and increased p CO 2 may have also affected sediment condition. Z. muelleri is able to maintain an oxic microshield around its roots by pumping oxygen from its leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies addressing cold adaptation in bacteria and eukaryotes have tended to focus on cold shock rather than cold growth. Moreover, few studies have described the molecular responses of cold‐adapted microorganisms (Rabus et al ., 2002), and no proteomic or microarray studies have reported the identification of genes involved in cold adaptation. This study therefore provides the first view of global gene expression in cold‐adapted microorganisms and is a benchmark for comparative studies in other organisms.…”
Section: Introductionmentioning
confidence: 99%
“…A few species of SRB have been recently subjected to genome sequencing (http://www.tigr.org;http://www.regx.de) . However, only a few studies have considered the adaptative responses and regulatory mechanisms in SRB when they are subjected to changes in physical and chemical conditions in the environment (Rabus et al ., 1993; 2002).…”
Section: Introductionmentioning
confidence: 99%